Synthesis and SAR of calcitonin gene-related peptide (CGRP) antagonists containing substituted aryl-piperazines and piperidines. Issue 4 (15th February 2016) - Civiello, Rita L.; Han, Xiaojun; Beno, Brett R.; Chaturvedula, Prasad V.; Herbst, John J.; Xu, Cen; Conway, Charles M.; Macor, John E.; Dubowchik, Gene M.
Graphical abstract: Abstract: Calcitonin gene-related peptide (CGRP) is a potent neuropeptide implicated in the pathophysiology of migraine. In the course of seeking CGRP antagonists with improved oral bioavailability, metabolic stability, and pharmacokinetic properties, lower molecular weight, structurally simpler piperidine and piperazine analogs of BMS-694153 were prepared. Several were found to have nM binding affinity in vitro. The synthesis and SAR of these substituted piperidine and piperazine CGRP antagonists are discussed.